Hubungan Peran Kepemimpinan dan Lingkungan Kerja dengan Organizational Citizenship Behavior di SMK Negeri 1 Air Putih Kabupaten Batubara - Shouma Fithria; Sjahril Effendy; Dedi Sahputra (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine the relationship between leadership roles and work environment with Organizational Citizenship Behavior at SMK Negeri 1 Air Putih, Batubara Regency. The hypothesis proposed is that there is a positive and significant relationship between the role of leadership and the work environment with Organizational Citizenship Behavior at SMK Negeri 1 Air Putih, Batubara Regency. The population in this study amounted to 35 people. The sampling technique used was purposive sampling. The data collection method is the scale of leadership roles, work environment and OCB. Data analysis using multiple regression analysis model. The results of this study are: 1. There is a positive and significant relationship between leadership roles and OCB. This is indicated by the coefficient value of 0.888 with the value of sig. 0.000 < 0.05 and it is stated that Ha is accepted with a very strong relationship. 2. There is a positive and significant relationship between the work environment and OCB. This is indicated by the coefficient value of 0.929 with the value of sig. 0.000 < 0.05 and it is stated that Ha is accepted with a very strong relationship. 3. There is a positive and significant relationship between leadership roles and work environment with OCB. This is indicated by the value of the correlation coefficient (R) = 0.952 with a value of sig. 0.000 < 0.05 and it is stated that Ha is accepted with a very strong relationship. The total effective contribution of leadership roles and work environment with OCB is 90.6% and is declared very strong